Replication studies in top management journals: An empirical investigation of prevalence, types, outcomes, and impact - Jörn H. Block; Christian Fisch; Narmeen Kanwal; Solvej Lorenzen; Anna Schulze (Management Review Quarterly, 2022)
Replication studies are important for the empirical research process. Yet, while there is an increased awareness of the need for replication in management research, it appears that such studies are rarely published in leading management journals. Importantly, we lack a comprehensive overview of replication studies in the top management journals that spans all sub-disciplines. Our systematic review closes this gap and provides an overview of the prevalence, types, outcomes, and impact of replication studies in management journals. We find that differences in the prevalence of replications between sub-disciplines exist and that most replications are wide replications. With regard to the replication outcome, our review shows that the share of non-confirming replications is low. Moreover, such replications are cited less often than confirming replications pointing towards a confirmation bias in management research. We discuss the implications of our results for authors, reviewers, and editors of management journals.
Keywords: 650; Replication; Independent replication; Systematic review; Impact; Empirical research